2021
DOI: 10.15252/emmm.202113977
|View full text |Cite
|
Sign up to set email alerts
|

A Norrin/Wnt surrogate antibody stimulates endothelial cell barrier function and rescues retinopathy

Abstract: The FZD4:LRP5:TSPAN12 receptor complex is activated by the secreted protein Norrin in retinal endothelial cells and leads to bcatenin-dependent formation of the blood-retina-barrier during development and its homeostasis in adults. Mutations disrupting Norrin signaling have been identified in several congenital diseases leading to hypovascularization of the retina and blindness. Here, we developed F4L5.13, a tetravalent antibody designed to induce FZD4 and LRP5 proximity in such a way as to trigger bcatenin si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 36 publications
1
50
0
Order By: Relevance
“…Activation of FZD4 signaling induces protein expressions for vascular barrier functions (e.g., claudin-5 [Cldn5], zonula occludens-1 [Zo-1], major facilitator superfamily domain containing 2 [Mfsd2]) and reduces the expression of plasmalemma vesicle-associated protein (Plvap), a marker of immature or leaky retinal vessels, 23 25 which restrains vascular leakage. Additionally, it has been shown that intravitreal injection of Norrin can restore the BRB properties to some degree in streptozotocin-induced diabetic rats 26 and that stabilizing β-catenin in the choriocapillaris switches its permeable nature to a BRB-like state.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of FZD4 signaling induces protein expressions for vascular barrier functions (e.g., claudin-5 [Cldn5], zonula occludens-1 [Zo-1], major facilitator superfamily domain containing 2 [Mfsd2]) and reduces the expression of plasmalemma vesicle-associated protein (Plvap), a marker of immature or leaky retinal vessels, 23 25 which restrains vascular leakage. Additionally, it has been shown that intravitreal injection of Norrin can restore the BRB properties to some degree in streptozotocin-induced diabetic rats 26 and that stabilizing β-catenin in the choriocapillaris switches its permeable nature to a BRB-like state.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that endocytosis of FZD4 in Norrin/Fzd4/β-catenin signaling axis is an important mechanistic step to maintaining iBRB and low PLVAP levels [ 20 ]. A more recent study showed that an FZD4/LRP5 agonist fully or partially restored transcellular iBRB function (associated with suppressed PLVAP levels and extravasated FITC dextran) with or without the amelioration of aberrant angiogenesis, respectively, in young (P20) or adult (3-month-old) Tspan12 −/− Wnt-deficient mouse retinas [ 134 ], further supporting the role of PLVAP in iBRB.…”
Section: Wnt Signaling and Ibrb Maintenancementioning
confidence: 88%
“…Methods to target Wnt signaling have been explored as potential therapeutics to restore iBRB in both development and diseases. Recently, Chidiac and colleagues [ 134 ] developed a bispecific antibody (F4L5.13) to trigger FZD4 and LRP5 proximity such that β-catenin signaling is activated. The stimulation of cultured ECs with the antibody caused the reversal of VEGF-induced permeability, partially by promoting surface expression of the junctional proteins ZO-1, claudin3, and claudin5.…”
Section: Wnt Signaling and Ibrb Maintenancementioning
confidence: 99%
See 2 more Smart Citations